Plasma TAFI Antigen Variations in Healthy Subjects - Chetaille, P.; Alessi, M. C.; Kouassi, D.; Morange, P. E.; Juhan-Vague, I. (Thrombosis and Haemostasis, 2000)
The Thrombin Activatable Fibrinolysis Inhibitor (TAFI) is a recently described inhibitor of fibrinolysis. The physiological variations of plasma TAFI antigen are not well known. We studied TAFI antigen values in healthy populations with a commercially available kit from Milan Analytica (Switzerland). Broad range of TAFI antigen values (from 41% to 259%) was found in a population of 249 healthy individuals. Gender as well as pregnancy did not influence mean values of TAFI antigen. There was a positive correlation between TAFI antigen and age in female (r = 0.28; p <0.05) but not in male populations. Mean TAFI antigen value of a black African male group [mean ± SD (range): 87 ± 23 (39-144%)] was significantly lower than the one of age matched Caucasian men [114 ± 34 (52-259%)] (p <0.0001). TAFI antigen values were very stable within individuals, they did not significantly vary on day time or at several months period.Thus, in contrast to large inter-individual variations, TAFI antigen levels are quite stable within individuals.
Keywords: TAFI; carboxypeptidase B; physiological variations; healthy population